A Critical Discourse Analysis of News Reports on Covid-19 in People’s Daily and The New York Times (Analisis Wacana Kritis Laporan Berita tentang Covid-19 di People’s Daily dan The New York Times) - Yin Yan Wang (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2021)
Critical Discourse Analysis aims to explore the ideology implicit in the discourse, thereby exposing the injustice, discrimination and prejudice in the discourse. The sudden epidemic has become the world's biggest event in 2020. Such international news is a special public discourse, and the discourse system and ideology displayed by various countries are different. This paper uses Fairclough’s Three-dimensional Framework and Halliday’s Systemic Functional Grammar as analysis tools, and selects 12 reports from the People’s Daily and The New York Times on the Covid-19 epidemic for Critical Discourse Analysis. After analysis, it is found that People’s Daily and The New York Times both use a lot of negative and derogatory terms, the difference in the focus of the media coverage of the two countries reflects the ideological difference caused by the cultural difference.